Investigation of optical energy band gap of transition metal oxide/polystyrene nanocomposite foils. (2022) - Barala, Monika; Siwach, Bulkesh; Sangwan, Reetu; Yadav, Kavita; Mohan, Devendra; Sanghi, Sujata
Abstract: In the present work, the optical properties of pure polystyrene, ZnO and AgO nanoparticles embedded polymeric foils were investigated. ZnO nanoparticles and AgO nanoparticles having size less than 50 nm were used. Pure polystyrene and ZnO, AgO nanoparticles embedded polystyrene foils were prepared by solution casting method. The investigated nanocomposite polymeric foils were highly transparent in the visible region, but due to strong absorbance in the UV region, absorbent peaks obtained at 364 nm and 250 nm, these foils act as an absorber in the UV region. PS/ZnO nanocomposite foils were characterized by transmittance and absorbance data that were obtained by UV–VIS spectrophotometer. The most important application of these foils is found to be in UV shielding and also based on the optical properties such as optical energy band was investigated, the PS/ZnO nanocomposite foils act as UV absorbent and a potential candidate for optoelectronic applications.